Analysis of Population, Poverty, Unemployment Rate, and Gini Ratio on Human Development Index in Bangka Belitung - Suhendra, Helen; Adam Indra Sakti; Muhammad Akbar Khaffi; Dalimunthe, Desy Yuliana; Haris Zirtana; Ridho Juniar; Diah Novita Sari; Muhammad Raqi Tama; Kristin Verahditiya (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2025)
The Human Development Index (HDI) is a measure that evaluates human development achievements based on fundamental quality-of-life components that can influence individual productivity levels. This study aims to analyze the impact of Population Size, Percentage of Poor Population, Open Unemployment Rate (TPT), and Gini Ratio on the Human Development Index (HDI) in the Bangka Belitung Islands Province from 2018 to 2023. The panel data regression method was employed, combining time series and cross-sectional data to provide more accurate information. The findings reveal that the HDI of the Bangka Belitung Islands Province has increased yearly, though it remains below the national average. The selected model was the Fixed Effect Model (FEM) based on the results of the Chow and Hausman tests. Analysis indicates that Population Size has a positive and significant effect on HDI, while the Percentage of Poor Population has a negative and not significant effect. Additionally, the Open Unemployment Rate (TPT) has a positive and significant effect on HDI, whereas the Gini Ratio has a negative and significant effect. Simultaneously, the four independent variables contributed 95.44% to HDI. These findings are expected to inform government efforts to improve human development quality, such as poverty alleviation, and highlight the need for attention to population management in balancing employment opportunities in the region and the government should work to reduce the unemployment rate through policies that focus on job creation, increasing workforce competitiveness, and addressing inequality, as reflected by the Gini ratio. This can be achieved by expanding equitable access to education and healthcare.